High Voter Participation during the Pandemic Covid-19 (Public Communication Success or Mass Mobilization of Single Candidates) - Roso Prajoko; Sri Hartini; Nurdini Tsabitul Chusna (LPPM Stikosa - AWS, 2023)
Politics in Boyolali Regency is controlled by the PDI-P with control of 35 seats for DPRD members in parliament, followed by the Golkar Party with 4 chairs, PKS with 3 chairs, PKB with 2 chairs and the Gerindra Party with 1 seat. With the majority of the number of DPRD members in parliament, PDI P rallied with all parties that won seats in parliament to nominate the incumbent as the sole regent candidate, except for the Prosperous Justice Party (PKS) which was neutral. Although only one pair of candidates participated, and it was carried out during the Covid-19 outbreak, the voter turnout rate in Boyolali was very high. This researcher will see, if the high participation is due to the success of political communication between the candidates and the KPU or whether there is a mass mobilization movement from the candidate for regent. This study uses a descriptive qualitative approach. The results of the election of a single candidate against an empty box are unattractive because there is no competition or power struggle. Even though it wasn't interesting, people still came to the polling station due to massive socialization from the Boyolali KPU.